Lumbociatalgia as presentation of a liposarcoma from psoas iliaco muscle: Case report - Pintado-Guevara, Carlos A. (2020)
Introduction. Retroperitoneal sarcomas are rare tumors, with a clinical presentation given by poorly specific compression symptoms. Case Report: We report a case of a 69-year-old man with a history of lumbociatalgia and an increase in the volume of the left lower limb until he was unable to wander, he underwent a Contrast Abdominal Tomography where a large tumor dependent on the left iliac psoas muscle was found, that extended to the pelvis, which was biopsied, finding a highly cellular psoas Liposarcoma. Conclusions: Sarcomas are rare tumors originating from the mesequenchymal tissue, the vast majority of them have nonspecific symptoms and signs, being diagnosed late and despite the surgical management of the prognosis is poor.